Climate change and COVID-19: Assessing the vulnerability and resilience of U.S. Indigenous communities to syndemic crises - Stefan Wheat; Shasta Gaughen; James Skeet; Larry Campbell; Jamie Donatuto; Jacqualine Schaeffer; Cecilia Sorensen (Elsevier, 2022)
The rapid emergence of the COVID-19 pandemic and the insidiously evolving climate crisis represent two of the most pressing public health threats to Indigenous Peoples in the United States. Understanding the ways in which these syndemics uniquely impact Indigenous Peoples, given the existing health disparities for such communities, is essential if we are to address modifiable root causes of health vulnerability and devise effective and equitable strategies to protect and improve health in the evolving climate landscape. We explore the compounding burden of the COVID-19 pandemic and climate change on Indigenous Peoples' health, and present several case studies which outline novel Indigenous approaches and perspectives that address climate change, COVID-19 and future health threats.